Home-based primary care visits by nurse practitioners. Issue 6 (19th June 2022) - Sun, Chun-An; Parslow, Chad; Gray, Ja'Lynn; Koyfman, Irina; Hladek, Melissa deCardi; Han, Hae-Ra
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: With rapidly growing numbers of homebound older adults, the need for effective home-based health interventions is increasingly recognized. Advanced practice registered nurses (NPs) are one of the most common providers of home-based primary care. Limited information is available to address the scope and nature of NP-led home-based primary care and associated outcomes. Objective: To synthesize research evidence of NP visits in home-based primary care. Data Sources: Six electronic databases—PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, Cochrane, Web of Science, and Scopus—were searched to identify peer-reviewed research articles addressing home-based primary care interventions led by NPs. Independent screening resulted in 17 relevant articles from 14 unique studies to include in the review. Conclusions: Nurse practitioners provided health assessments, education, care planning and coordination primarily by face-to-face home visits. Despite a variability in terms of study design, setting, and sample, NP-led home-based primary care was in general associated with less hospitalization and fewer emergency department visits. Evidence was mixed in relation to patient-reported outcomes such as subjective health, functional status, and symptoms. Costs and patient or caregiver satisfaction were additional outcomes addressed, but the findings were inconsistent. Implications for Practice: Recent policy changes to authorize NPs to independently assess, diagnose, and order home care services directly affect how NPs approach home-based primary care programs. Our findings support NP-led home-based primary care to decrease consequential health utilization and suggest the need for further evaluating the care models in diverse populations with more patient-reported and caregiver outcomes.